AA.VV. (Azaola, B.; Desrues, T..; Larramendi, M. H. de; Planet, A. I. y Ramírez, A.) (eds.) (2022): Cambio, crisis y movilizaciones en el Mediterráneo Occidental, Granada, Comares, 441 pp. - Feliu Martinez, Laura (Política y Sociedad, 2023)
Reseña de la obra: AA.VV (Azaola, B; Desrues, T:; Larramendi, M. H. de; Planet, A.I; y Ramírez, A.) (eds.) (2022): Cambio, crisis y movilizaciones en el Mediterráneo Occidental, Granada, Comares, 441 p.